The Contemporary Issues of Food Security of the Bhuiya of Jharkhand - Sahu, Santanu (Arthshastra Indian Journal of Economics & Research, 2019)
Food is indispensable for existence. Hence, the issue of food security is a matter of great concern for the whole mankind. One needs to address the issue of food security at different levels: global, regional, household, and individual. The present paper dealt with food security status of the Bhuiya community of Palamu district of Jharkhand using primary data. It was found that the state of food security was grave among Bhuiya households. The community struggled for food for existence and there were no or few sustainable livelihood options available to them. This in turn made them vulnerable and food insecure, negatively affecting their productivity and efficiency and keeping them trapped in the vicious cycle of poverty and malnutrition.